2014
DOI: 10.1039/c4sm01972e
|View full text |Cite
|
Sign up to set email alerts
|

Relating foam and interfacial rheological properties of β-lactoglobulin solutions

Abstract: We have determined bulk rheology of b-lactoglobulin (BLG) foams and surface viscoelasticity of corresponding protein solutions by varying pH as well as type, valency and concentration of the added salt in a wide range. Foam rheology was characterized by the storage modulus G 0 , the apparent yield stress s y , and the critical strain g c,foam defining the cessation of the linear viscoelastic response. These quantities were determined at gas volume fractions f between 82% and 96%. Surface viscoelasticity was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…For instance, for foams stabilized by globular proteins such as β-lactoglobulin, G o is larger than the value predicted by Eq. (2) by up to an order of magnitude [4,15,34]. The enhancement of G o depends on the pH and on the ionic strength.…”
Section: Static Elasticitymentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, for foams stabilized by globular proteins such as β-lactoglobulin, G o is larger than the value predicted by Eq. (2) by up to an order of magnitude [4,15,34]. The enhancement of G o depends on the pH and on the ionic strength.…”
Section: Static Elasticitymentioning
confidence: 92%
“…The enhancement of G o depends on the pH and on the ionic strength. At a pH corresponding to the isoelectric point (pH = pH iep ), where proteins carry no net charge, the repulsion between molecules is reduced, leading to the formation of aggregates and networks across the films [15,34]. The strong mechanical reinforcement of the foams is attributed to this effect [15,34].…”
Section: Static Elasticitymentioning
confidence: 96%
“…In most applications the shear rheology of the particle-laden interface greatly influences the macroscopic performance of multiphase systems, especially the stability of emulsions and foams in dynamic environments 9,10 . The shear-induced deformation of emulsion droplets and foam bubbles, as well as the liquid drainage in the plateau-borders, can be strongly influenced by the degree of particle mobility and reorganization at the interface [11][12][13] . It has also been reported that the arrested coalescence of bubbles/droplets is related to the shear yield strength of the interfacial layer, as the deformation and breakup of the bubble/droplet is limited by the rigidity of the interface 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Stability against disproportionation has also been correlated with the higher interfacial dilatational elasticity E' of proteins [15]. Concerning foam rheology, it has been shown for β-lactoglobulin (β-lg) that a higher dilatational and shear interfacial elasticity can increase the yield stress and storage modulus of a foam [16].…”
Section: Introductionmentioning
confidence: 99%